Estimating retention in HIV care accounting for patient transfers: A national laboratory cohort study in South Africa. - Matthew P Fox; Jacob Bor; Alana T Brennan; William B MacLeod; Mhairi Maskew; Wendy S Stevens; Sergio Carmona (PLoS Medicine)
Background Systematic reviews have described high rates of attrition in patients with HIV receiving antiretroviral therapy (ART). However, migration and clinical transfer may lead to an overestimation of attrition (death and loss to follow-up). Using a newly linked national laboratory database in South Africa, we assessed national retention in South Africa's national HIV program. Methods and findings Patients receiving care in South Africa's national HIV program are monitored through regular CD4 count and viral load testing. South Africa's National Health Laboratory Service has maintained a database of all public-sector CD4 count and viral load results since 2004. We linked individual laboratory results to patients using probabilistic matching techniques, creating a national HIV cohort. Validation of our approach in comparison to a manually matched dataset showed 9.0% undermatching and 9.5% overmatching. We analyzed data on patients initiating ART in the public sector from April 1, 2004, to December 31, 2006, when ART initiation could be determined based on first viral load among those whose treatment followed guidelines. Attrition occurred on the date of a patient's last observed laboratory measure, allowing patients to exit and reenter care prior to that date. All patients had 6 potential years of follow-up, with an additional 2 years to have a final laboratory measurement to be retained at 6 years. Data were censored at December 31, 2012. We assessed (a) national retention including all laboratory tests regardless of testing facility and (b) initiating facility retention, where laboratory tests at other facilities were ignored. We followed 55,836 patients initiating ART between 2004 and 2006. At ART initiation, median age was 36 years (IQR: 30-43), median CD4 count was 150 cells/mm3 (IQR: 81-230), and 66.7% were female. Six-year initiating clinic retention was 29.1% (95% CI: 28.7%-29.5%). After allowing for transfers, national 6-year retention was 63.3% (95% CI: 62.9%-63.7%). Results differed little when tightening or relaxing matching procedures. We found strong differences in retention by province, ranging from 74.2% (95% CI: 73.2%-75.2%) in Western Cape to 52.2% (95% CI: 50.6%-53.7%) in Mpumalanga at 6 years. National attrition was higher among patients initiating at lower CD4 counts and higher viral loads, and among patients initiating ART at larger facilities. The study's main limitation is lack of perfect cohort matching, which may lead to over- or underestimation of retention. We also did not have data from KwaZulu-Natal province prior to 2010. Conclusions In this study, HIV care retention was substantially higher when viewed from a national perspective than from a facility perspective. Our results suggest that traditional clinical cohorts underestimate retention.